Perbudakan yang Baru : Kritik atas Pencerahan dari Theodor Adorno - Karundeng, Yustinus Realino; Jamlean, Anselmus (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2025)
This paper explores Theodor W. Adorno’s critique of the Enlightenment project. Originally intended to liberate humanity from myth and superstition, the Enlightenment, according to Adorno, ultimately gave rise to a new form of domination through instrumental rationality. Alongside Max Horkheimer in Dialectic of Enlightenment, Adorno argued that reason in modern society has become a tool of control rather than emancipation. The Enlightenment, they claim, created a “new myth” through technocratic rationality, leading to authoritarian social structures and reducing individuals to objects within systems of power. Adorno identifies this rationality as a form of modern slavery, masked by ideals of humanism and progress. In response, he proposed negative dialectics, a method that reveals hidden contradictions in social systems and challenges linear ideas of progress. Through this approach, Adorno underscores the need for continuous critique of reason and power to safeguard human dignity and freedom in the face of modernity’s oppressive tendencies.